Research on soft x-rays in high-current plasma-focus discharges and estimation of plasma electron temperature. (3rd August 2016) - Skladnik-Sadowska, E; Zaloga, D; Sadowski, M J; Kwiatkowski, R; Malinowski, K; Miklaszewski, R; Paduch, M; Surala, W; Zielinska, E; Tomaszewski, K
Abstract: The paper presents results of experimental studies of dense and high-temperature plasmas, which were produced by pulsed high-current discharges within a modernised PF-1000U facility operated at different initial gas conditions, and supplied from a condenser bank which delivered energy of about 350 kJ. The investigated discharges were performed at the initial deuterium filling under pressure of 1.6–2.0 hPa, with or without an additional puffing of pure deuterium (1 cm 3, under pressure 0.15 MPa, at instants 1.5–2 ms before the main discharge initiation). For a comparison discharges were also performed at the initial neon filling under pressure of 1.1–1.3 hPa, with or without the addition of deuterium puffing. The recorded discharge current waveforms, laser interferometric images, signals of hard x-rays and fusion neutrons, as well as time-integrated x-ray pinhole images and time-resolved x-ray signals were compared. From a ratio of the x-ray signals recorded behind beryllium filters of different thickness there were estimated values of a plasma electron temperature ( T e ) in a region at the electrode outlets. For pure deuterium discharges an averaged T e value amounted to 150–170 eV, while for neon discharges with the deuterium puffing it reached 330–880 eV (with accuracy of ±20%).